iHELP Smart Roadside Assistance / Mohammad Nur Shahrin Mohd Razmi - Mohd Razmi, Mohammad Nur Shahrin (2013)
Roadside assistance means getting for someone helps when vehicle broke down. Breakdown cover is often closely related to roadside assistance. Not many of road users use their insurance company help line to get assistance. The most common action taken is by contact their family or friends. They also tried to detain the other road users. The problems are they maybe not having expertise to fix it. Not many road users today who want to give help especially in a remote area because fear of robber tricks. This is because the road users do not have information about the nearby workshop to contact especially when travel to other districts or states. To overcome the problems, some solution has been discovered. It is a smart roadside assistance mobile application that can help road users to get assistance from the nearby workshop. By using iHelp Smart Roadside Assistance application, road users just simply press the HELP button and wait the respond from the server. The server will calculate the driving distance between users and workshops using Google Maps in order to find the nearest workshop. Server then will response back to users when it gets the workshop that able to give help. In order to complete research and development of this project. Software Development Life Cycle (SDLC) methods use as a guideline. Start with preliminary study of the domain area and analysis the requirement to develop the system. Then, system development processes follow by testing and evaluation. The last phase is end by complete the thesis report. The functionality of iHelp Smart Roadside Assistance has been tested using the real data. The usability of this application evaluated by conduct a set of questionnaires to the random respondents. The feedback received from the respondents is very positive. This application is potential to introduce to the road users for the whole Malaysia.